Morphological Review in the Subtitle of “The Social Dilemma” Movie and Its Translation Quality - Trisnawati, Nia; Adika, Dimas (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This research focuses on the quality of translation used in the movie “The Social Dilemma” through a morphological analysis. By exploring the film as a whole and then using a purposive sampling technique, the researchers selected terms that aligned with the objectives of this study. Using the theory from Garvey and Delahunty (2010), Hana and Feldman (2013), and Zapata (2000), the researchers found 7 types of words formation, which are affixation, compounding, abbreviation, conversion, coinage, borrowing, and blending. Through the process of identification, this study found some translation quality issues by elaborating those 7 types of word formation which were explained based on Nababan, Nuraeni, and Sumardiono (2012) theory in terms of their accuracy, acceptability, and readability. This study provides readers with an understanding of the types of morphological terms used and aims to benefit future researchers.